2010
DOI: 10.1111/j.1600-0404.2010.01325.x
|View full text |Cite
|
Sign up to set email alerts
|

Sleep habits and sleep complaints in Austria: current self-reported data on sleep behaviour, sleep disturbances and their treatment

Abstract: Subjectively reported sleep disorders proved to be relatively stable between 1993 and 2007.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 16 publications
3
11
0
1
Order By: Relevance
“…Given the ready availability and convenience of hypnosedatives, it may simply reflect habits of a society that uses hypnotics easily as shown by various different authors in industrialized countries. [2][3][4]29…”
Section: Experience With Hypnoticsmentioning
confidence: 99%
“…Given the ready availability and convenience of hypnosedatives, it may simply reflect habits of a society that uses hypnotics easily as shown by various different authors in industrialized countries. [2][3][4]29…”
Section: Experience With Hypnoticsmentioning
confidence: 99%
“…Our results seem to confirm those reported recently by Schlesinger et al (7) who found that cholesterol was significantly associated with RLS compared with subjects without RLS. Both RLS (13)(14)(15) and OSA (16,17) are frequent clinical conditions in the population (3-5% and 3-14%, respectively); thus, the association between RLS and OSA is not surprising at all and has been known for decades (18,19). This type of control was not performed in the study by Schlesinger et al (7) in which sleep disturbances were assessed essentially by a questionnaire and an interview.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, we performed a relatively large number of polysomnographic recordings that allowed us to detect a high number of patients with significant OSA, and maybe, we have also missed some of them in the 18 patients who were not recorded polysomnographically. Both RLS (13)(14)(15) and OSA (16,17) are frequent clinical conditions in the population (3-5% and 3-14%, respectively); thus, the association between RLS and OSA is not surprising at all and has been known for decades (18,19). More recent studies have suggested that RLS can affect between 2% and 4.5% of patients with OSA (20,21).…”
Section: Discussionmentioning
confidence: 99%
“…Az AIS alapján igazolódott a magánéleti stressz (p = 0,001) és fájdalom hatása (p = 0,033). Zeitlhofer osztrák felmérésében is hasonló okokat neveztek meg leggyakrabban: személyes problémák (23%), a nap eseményei (22%), fájdalom (16%), munkahelyi problémák (13%) [20].…”
Section: Megbeszélésunclassified